2000
DOI: 10.1111/j.1530-0277.2000.tb04634.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism Susceptibility Loci: Confirmation Studies in a Replicate Sample and Further Mapping

Abstract: Analyses of a second large sample of alcoholic families provided further evidence of genetic susceptibility loci on chromosomes 1 and 7. Genetic analyses also have identified susceptibility loci on chromosomes 2 and 3 that may act only in one of the two data sets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
124
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 231 publications
(131 citation statements)
references
References 54 publications
5
124
2
Order By: Relevance
“…A second region which includes markers D1S196 and D1S2878 is within 1 cM of the gene for an aldehyde dehydrogenase (ALDH9), an enzyme that catalyzes gamma aminobutylaldehyde to GABA. The region near D1S230 has previously been reported by the COGA group to give evidence for linkage Foroud et al, 2000;Nurnberger et al, 2001;Dick et al, 2002]. In the present study, multipoint linkage analysis showed a LOD value of 3.46 (P = 0.002) for marker D1S196 [181.49 cM Marshfield] and a similar LOD value (3.45) at the adjacent marker D1S2878 using a three covariate model that included age, gender, and constraint.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A second region which includes markers D1S196 and D1S2878 is within 1 cM of the gene for an aldehyde dehydrogenase (ALDH9), an enzyme that catalyzes gamma aminobutylaldehyde to GABA. The region near D1S230 has previously been reported by the COGA group to give evidence for linkage Foroud et al, 2000;Nurnberger et al, 2001;Dick et al, 2002]. In the present study, multipoint linkage analysis showed a LOD value of 3.46 (P = 0.002) for marker D1S196 [181.49 cM Marshfield] and a similar LOD value (3.45) at the adjacent marker D1S2878 using a three covariate model that included age, gender, and constraint.…”
Section: Discussionsupporting
confidence: 72%
“…The chromosome 4 region extended 38 cM near D4S2393 and D4S2361 [69.6 cM] and had a LOD score of 2.50. Results of genotyping a replication sample of 157 COGA families supported the linkage findings for chromosome 1 for marker D1S1588, with the combined sample decreasing to LOD = 2.6 [Foroud et al, 2000]. The linkage reported for chromosome 7 at D7S821 increased in the combined data to LOD = 2.9.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…20,21 This association was recently supported by a family-based study using genetic fine-mapping of the 1p region of chromosome 1. 29 Comparing gentoype frequencies in our study with previous research (Begni et al, 30 30 who reported lower genotype frequencies of the GRIK3 polymorphism Ser allele in his sample of schizophrenic patients.…”
Section: Discussionmentioning
confidence: 79%
“…18 The GluR7 subunit of KA receptors has been mapped to chromosome 1 at 1p34-p33, 19 close to a region reported to be associated with alcoholism and alcoholism-related phenotypes from linkage studies. [20][21][22] GluR7 receptor subunits form a functional homomeric receptor channel with low sensitivity to glutamate. 23 The GluR7 contains an exonic thymine/guanine nucleotide variation that determines a serine or alanine at position 310 in the N-terminal extracellular domain of the receptor.…”
Section: Introductionmentioning
confidence: 99%